Clinical response to lifestyle counseling for dyslipidemia and elevated blood pressure in childhood cancer survivors. Issue 1 (3rd November 2022) - Javalkar, Karina; Huang, Yisong; Lyon, Shannon M.; Palfrey, Hannah; Hartz, Jacob; Chen, Ming Hui; de Ferranti, Sarah
Abstract: Background: Childhood cancer survivors (CCS) have increased risk of premature cardiovascular disease. Whether they respond similarly to lifestyle changes for elevated blood pressure (BP), body mass index (BMI), and dyslipidemia to those without history of childhood cancer is unknown. Procedure: This retrospective cohort study included CCS and 3:1 age‐ and sex‐matched controls treated at Boston Children's Hospital Preventive Cardiology (2010–2019) using lifestyle management based on National Heart, Lung, and Blood Institute (NHLBI) guidelines. Change in BMI, BP, and lipids were analyzed. Results: We included 52 CCS and 162 controls with a median age of approximately 16 years. More CCS (84.3%) had elevated baseline fasting triglycerides (TG) than controls (49.4%) ( p < .001). More CCS (62.5%) also had abnormal baseline high‐density lipoprotein cholesterol (HDL‐C) compared to controls (35.2%) ( p = .001). Baseline BMI, BP, total cholesterol (TC), and low‐density lipoprotein cholesterol (LDL‐C) were similar between groups. Over 15 weeks [IQR: 10.5–26], CCS had greater decrease in TG than controls (72.5 vs. 17 mg/dl decrease, p = .095). BP improved in 5% of CCS versus 38% of controls ( p = .008). For both, BMI, TC, LDL‐C, and HDL‐C remained stable. CCS with stem cell transplantation (SCT) had a TC increase of 5% (6 mg/dl) compared to a decrease of 9% (19 mg/dl) among CCS without SCT ( p = .02). Conclusions: CCS demonstrated similar improvement in lipids, but impaired BP lowering in response to lifestyle management compared to controls. Further prospective studies are needed to determine if earlier pharmaceutical treatment is warranted in this higher risk population and for the long‐term risk reductions of these approaches.